DTCF: deadline task consolidation first for energy minimisation in cloud data centres. (2018) - Sanjeevi, P.; Viswanathan, P.
The consumption of energy is a vital issue in the cloud, when more precisely administering a large-scale data centre. The cloud data centre accommodating more hosts consume an extent of energy for computation which increases the consumption of energy. To handle this issue, we propose a heuristics energy-efficient workload consolidation with deadline constraint to optimise energy in cloud data centre. The deadline task consolidation first algorithm ranks hosts for creating virtual machines (VMs) and validates the processing time of VMs and places the VM considering deadline of tasks, VMs can be placed in an increasing order of their respective processing time. Then, the decision for migrating VMs to other hosts is evaluated using Markov decision model. Through this process, for specific virtual machine necessities of workloads, we can reduce the number of hosts. The proposed algorithm is simulated in Cloudsim shows that it improves the workload consolidation quality, and is appropriate for deadline task consolidation in cloud data centre.